Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pemerintah Provinsi Kalimantan Timur Tahun 2021 – 2024 - Melia Fauzia; Hendra Saputra; Galih Supraja (International Journal of Economics and Management, 2026)
This Study aims to analyze the financial performance of the East Kalimantan Provincial Government based on the financial independence ratio, effectiveness ratio, and efficiency ratio during the 2021–2024 period. The study employs a descriptive quantitative approach using quantitative secondary data obtained from Budget Realization Reports published by the Audit Board of Indonesia (BPK). Data were collected through documentation and literature review techniques. The data analysis technique used was descriptive quantitative analysis by calculating and interpreting regional financial ratios to assess the level of the provincial government's financial performance. The results indicate that the financial performance of the East Kalimantan Provincial Government from 2021 to 2024 was generally categorized as good, with an average financial independence ratio of 125%, classified as high; an effectiveness ratio of 114%, classified as effective; and an efficiency ratio of 163%, classified as less efficient. The findings show a high level of financial independence and strong effectiveness in locally generated revenue (PAD). However, further optimization of revenue generation and expenditure control is needed to improve efficiency and achieve a more balanced budget.